Long road to freedom : the advocate history of the gay and lesbian movement - Thompson, Mark; Daly, Deborah (New York : St. Martin's Press, 1994)
Fonds Suzan Daniel (FSD)
Engels
Monografie
Keywords: homobewegingen; lesbische vrouwen